Development of Tunable Nanocomposites Made from Carbon Nanotubes for Electrochemical Applications - Esplandiu, Maria Jose; Baeza, Mireia; Olive-Monllau, Rosa; Cespedes, Francisco; Bartroli, Jordi (IntechOpen, 2011)
None